The Impact of Polypharmacy on Elderly Patients and Strategies to Reduce Risks - Dale, Ashwini; Kashid, Girish (Journal of Neonatal Surgery, 2025)
Polypharmacy, the concurrent use of multiple medications, is increasingly prevalent among elderly patients, posing significant risks to their health and well-being. This paper explores the multifaceted impact of polypharmacy, highlighting its contribution to adverse drug reactions (ADRs), cognitive decline, hospitalizations, and decreased quality of life. Through a comprehensive review of existing literature and data analysis, the paper identifies key risk factors associated with polypharmacy in elderly populations. It further proposes evidence-based strategies to mitigate these risks, including medication review programs, deprescribing initiatives, and patient- centered care models. Case studies and statistical insights illustrate the practical application of these strategies, underscoring the critical role of healthcare providers in managing polypharmacy. The findings emphasize the importance of collaborative efforts among physicians, pharmacists, and patients to optimize medication regimens, reduce unnecessary prescriptions, and enhance patient outcomes. Future research directions are discussed to address existing gaps and foster the development of innovative approaches for minimizing polypharmacy-related risks in aging populations.